Model averaging in factor analysis: An analysis of Olympic decathlon data - Schomaker, M.; Heumann, C. (Journal of Quantitative Analysis in Sports, 2011)
This article presents a multivariate analysis of Olympic decathlon data based on maximum likelihood factor analysis. All results explicitly account for model selection uncertainty, which is inherent in any data-based selection process but mostly ignored in reports related to multivariate sports data. For this purpose, some well-established frequentist procedures that have so far been applied almost exclusively to regression analysis are adopted and transferred to the factor analytical context. The findings support the claim that decathlon contests consist of three dimensions. These dimensions seem to be similar to, but not exactly the same, as those found by Cox and Dunn (2002) via hierarchical cluster analysis.